Late Oligocene-early Miocene birth of the Taklimakan Desert - Zheng, H.; Wei, X.; Tada, R.; Clift, P.; Wang, B.; Jourdan, Fred; Wang, P.; He, M. (National Academy of Sciences, 2015)
As the world’s second largest sand sea and one of the most important dust sources to the global aerosol system, the formation of the Taklimakan Desert marks a major environmental event in central Asia during the Cenozoic. Determining when and how the desert formed holds the key to better understanding the tectonic–climatic linkage in this critical region. However, the age of the Taklimakan remains controversial, with the dominant view being from ~3.4 Ma to ~7 Ma based on magnetostratigraphy of sedimentary sequences within and along the margins of the desert. In this study, we applied radioisotopic methods to precisely date a volcanic tuff preserved in the stratigraphy. We constrained the initial desertification to be late Oligocene to early Miocene, between ~26.7 Ma and 22.6 Ma. We suggest that the Taklimakan Desert was formed as a response to a combination of widespread regional aridification and increased erosion in the surrounding mountain fronts, both of which are closely linked to the tectonic uplift of the Tibetan–Pamir Plateau and Tian Shan, which had reached a climatically sensitive threshold at this time.